The Antecedents of Express Delivery Service Company Selection and Customer Satisfaction: Behavioral Intention from Bangkok, Thailand - Lertatthakornkit , Dr.Tippawan; Ziaul Zafri, Mr.Kazi; Bangbon, Dr.Pensri (Journal of Dhamma for Life, 2023)
In the fiercely competitive landscape of the e-commerce sector, behavioral intention and customer satisfaction play pivotal roles in the pursuit of gaining a competitive edge for express delivery companies. This research endeavor is designed to comprehensively investigate the antecedent factors that exert influence on customer behavior and satisfaction when they are in the process of selecting express delivery service providers in the vibrant market of Bangkok, Thailand. To conduct this study, a robust sample size of 321 respondents has been meticulously selected, and Structural Equation Modeling (SEM) has been employed as the analytical technique of choice. Our research findings shed light on the following key insights: Personal Contact Quality, Payment Method, and Order Information Sharing emerge as significant determinants that significantly impact customer satisfaction within the context of express delivery services in Bangkok. On the contrary, factors such as Delivery Service, Marginal Delivery Cost, Short Delivery Time, and Order Condition have been identified as statistically insignificant in their influence on customer satisfaction. Moreover, our study uncovers a significant and positive relationship between customer satisfaction and the decision-making process in favor of selecting an express delivery service company. These insights have profound implications for express delivery service providers, offering valuable guidance in terms of customer attraction, retention, and the attainment of competitive advantages. Furthermore, our study extends its significance beyond the industry, as it provides actionable insights for government entities to formulate guidelines that serve the interests of both customers and express delivery companies.